Effects of ferrite and graphite phases on scratch characteristics of nodular cast iron - Zhitong Xu; Ming Liu; Chenghui Gao; Fuqian Yang (Journal of Materials Research and Technology, 2024)
In this work, we conduct micro-scratch tests of nodular cast iron with Vickers indenter under constant normal load and investigate the effects of individual phases (i.e., ferrite and graphite phases) on the scratch characteristics of nodular cast iron. Using a bimodal Gaussian model to fit the experimental data of penetration depth, residual depth, elastic recovery rate, and scratch hardness, we calculate the contribution percentages of individual phases to scratch variables. The scratch variables are independent of the scratch speed used in this work, while the penetration depth increases linearly with increasing the normal load. There exists a large difference between the contribution percentages and the volume fractions calculated from SEM images and XRD pattern. Such a large difference suggests that the bimodal Gaussian distribution analysis does not include the effect of the interaction between two phases on the scratch characteristics of dual-phase materials with significantly distinct mechanical properties and geometrical dimensions. A more refined method taking into account the interaction between two phases needs to be developed for the analysis of the scratch characteristics of dual-phase materials.